Metaverse: Deconstruction and Differentiation of Identity Under the New Media Environment - Mao, Xuhui; Li, Xuan; Lu, Wenli; Li, Yazheng (Advances in Social Sciences Research Journal, 2023)
The meta-universe is a new media scene based on VR and other technologies. Whether it will cause greater estrangement between people or even social disintegration or high-latitude healing in the future, the key lies in understanding the inner path of people's spiritual communication. From the perspective of the critical school, based on identity, this paper systematically analyzes and demonstrates the performance, causes, and risks of the deconstruction of identity by new media scenarios through a questionnaire survey on the correlation between virtual identity and real identity and adopts the interview method, to explore the social management of the metauniverse under the perspective of identity. By revealing the interaction between the virtual symbolic identity and the real identity, the paper seeks the value compliance of shaping a positive international image of the world with the help of the meta-universe. The research finds that: the hyperreal experience allows users to create and identify with a new self, the role deviation brought by the utopian world affects identity, the privacy leakage in the real world depends on the degree of identity, and the metauniverse challenges the national discourse system.